2014
DOI: 10.1002/eji.201343998
|View full text |Cite
|
Sign up to set email alerts
|

CD5 enhances Th17‐cell differentiation by regulating IFN‐γ response and RORγt localization

Abstract: Mechanisms that modulate the generation of Th17 cells are incompletely understood. We report that the activation of CK2 by CD5 is essential for the efficient generation of Th17 cells in vitro and in vivo. The CD5-CK2 signaling pathway enhanced TCR induced activation of AKT and promoted the differentiation of Th17 cells by two independent mechanisms: inhibiting GSK3, and activating mTOR. Genetic ablation of the CD5-CK2 signaling pathway attenuated TCR induced AKT activation and consequently increased activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 21 publications
(41 reference statements)
2
26
1
Order By: Relevance
“…We found that loss of CD5-CK2 signaling had not effect on OVAp induced pS13-CDC37, the site of CK2 phosphorylation (Fig 5B). These findings suggest pAkt/pCDC37 signaling axis is not regulated via CD5-CK2 signaling in developing T lymphocytes unlike previous findings in peripheral T lymphocytes [11]. …”
Section: Resultscontrasting
confidence: 92%
See 3 more Smart Citations
“…We found that loss of CD5-CK2 signaling had not effect on OVAp induced pS13-CDC37, the site of CK2 phosphorylation (Fig 5B). These findings suggest pAkt/pCDC37 signaling axis is not regulated via CD5-CK2 signaling in developing T lymphocytes unlike previous findings in peripheral T lymphocytes [11]. …”
Section: Resultscontrasting
confidence: 92%
“…In peripheral T cells, CD5-CK2 signaling is necessary for efficient TCR-induced activation of Akt to promote cell survival [11]. We found no difference in the activation of Akt in DP or SP thymocytes under basal conditions or following OVAp injection between CD5-WT and CD5-ΔCK2BD mice (Fig 5A).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Furthermore, considering the fact that ATRA-treated CCR6 + T cells maintain their Th17 features (42) and that mTORC1, via the induction of the kinase S6K2, is involved in the nuclear translocation of RORC (60,85), one other possibility is that mTOR inhibitors interfere with the RORC-mediated transcriptional program in Th17 cells, which is favorable to HIV replication (20). Consistent with this hypothesis, we demonstrated that decreased HIV replication in the presence of rapamycin and INK128 coincided with a significant reduction in IL-17A production by ATRA-treated CD4 + T cells.…”
Section: On Hiv Replication In Ccr6mentioning
confidence: 99%